DEVELOPMENT OF TECHNOLOGY FOR FUEL BRIQUETTES USING COKE BREEZE - A. R. Guseynova; N. A. Salimova; L. V. Huseynova (Литьë и металлургия)
It is shown that the received oil-coke pucks with application of coke granules can be used instead of liquid and gaseous fuel.